(untitled) (World Economics and Finance Bulletin, 2023)
This article discusses the issues of competitive selection of independent members of the Supervisory Board, its role and importance, expansion of its functions and tasks, the procedure for organizing and conducting competitive selection of independent members of the Supervisory Board